Chaiyu-Dixian Formula Exerts Protective Effects on Ovarian Follicular Abnormal Development in Chronic Unpredictable Mild Stress (CUMS) Rat Model - Xu, Hui-Xian; Lin, Shu-Xia; Gong, Yuewen; Huo, Zi-Xuan; Zhao, Cheng-Yun; Zhu, Hong-Mei; Xi, Sheng-Yan (Frontiers in Pharmacology, 2020)
Background: Chronic stress has been known to impair female reproductive function, but the mechanism remains to be further investigated. Chaiyu-Dixian Formula (CYDXF) has been reported to regulate human endocrine disorders clinically, however, whether this formula can affect chronic stress-induced ovarian follicular development is not clear. Aim of the study: To examine effects of CYDXF on follicular development and explore possible mechanism in a chronic unpredictable mild stress (CUMS) model. Materials and Methods: Adult female rats were randomly divided into 5 groups: control group, CUMS group (saline treatment), CUMS+Estradiol (E2) (0.1 mg/kg) group, CUMS+CYDXF (2.73 g/kg) group and CUMS+CYDXF (5.46 g/kg) group. Body weights and behavioral tests were documented. Serum hormone levels were determined by enzyme-linked immunosorbent assay (ELISA). Western blotting was used to detect the protein levels in the PI3K/Akt pathway and brain-derived neurotrophic factor (BDNF). The follicles were analyzed and classified according to their morphological characterization. Results: CYDXF relieved depression-like behaviors and ameliorated the abnormality in rat estrous cycle in rat model of CUMS. Moreover, CYDXF could regulate endocrine disorders, increase the proportion of antral follicles as well as decrease the proportion of follicular atresia, which suggested that CYDXF could alleviate abnormal follicular development and improve overall ovarian function. Furthermore, CYDXF also activated BDNF-mediated PI3K/Akt signaling pathway. Conclusions: CYDXF (at dose of both 2.73 and 5.46 g/kg) attenuated chronic stress-induced abnormal ovarian follicular development by relieving depression-like behaviors and improving ovarian function through partly the regulation of BDNF-mediated PI3K/Akt pathway.